Burkina Faso : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This paper assesses the link between public investment and economic growth in Burkina Faso. It also evaluates Burkina Faso's external competitiveness by using a comparison of REER to its equilibrium levels and a survey-based assessment of overall competitiveness. The report attempts to quantify the impact of rainfall and terms-of-trade shocks on the Burkinabe economy and draws policy measures to lessen external shocks. The report assesses that industrial mining has become a source of foreign exchange and government revenue, which requires transparent management and accountability.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet